O Colégio Agrícola de Francisco Beltrão e os desafios da educação politécnica - Costa, Nara Tatiana (2016)
The reason of this research, located in the line of research Society, Knowledge and Education, the Program of Graduate Studies in Education, Master Course, the State University of Western Paraná, Campus Francisco Beltrão, is to analyze the challenges of polytechnic education in the context of the Agricultural College of Francisco Beltrão/PR. Centered education in the midst of two inseparable elements, education and work, which was the main issue of research: to analyze the principles of polytechnic education may be present in the educational practices of the Agricultural College. Thus we have as complementary objectives: understanding the context of the field and the relationship with their young; identify theoretical and methodological elements of Polytechnic Education and some of his experiences as a reference for our analysis; characterize the educational project of the East and vocational education that is developed at the Agricultural College; analyze the relationship between work and education in the theoretical and practical teaching, tracing elements to demarcate how such relationships happen; systematize and analyze the educational practices developed in the Agricultural College. Stand out from the central and complementary objective the central research questions: Educational practices in Agricultural College are developed on the principles of a polytechnic education? The educational practices of the Agricultural College, and they are organized, make students able to apply theoretical knowledge which they appropriate also in practice and vice versa? In this training, become equally able to reflect and interpret reality and understand the organization of this work in society and self organizing? In an effort to demonstrate how it materializes and translates into potential education, research led to a dip in the pedagogical practices Agricultural College. The methodology adopted the case study, which won qualitative characteristic to enable a broad deepening the object subsidized by the theoretical framework for the development of research. Presents the analysis of the collected data, it summarizes what he considers more significant in terms of pedagogical practices, with all its contradictions and limitations, as well as all its polytechnic education potential. He sought the theoretical references as Marx and Engels (2004), Lunatcharski (1988). Pistrak (2015), Shulgin (2013), Saviani (1989, 2003), Machado (2015) Market (1996), Nosella (2007), Manacorda (2007) Sousa Jr (2010), Rodrigues (1998) among others, clarify and exemplify what happens and how the relationship between theory and practice in a differentiated education project, with challenges and polytechnics possibilities. One of the challenges for a polytechnic education is to maintain the collective integrated a coherent educational project pedagogically. Do not just make the integration of disciplines, if there is an ideal of common education to all.